Microsoft Excel : a beginners' guide to pivot tables in Excel - Ashby, Deborah (Packt Publishing, 2021)
Pivot Tables separate beginners from intermediates and allow you to delve deep into your data like no other tool can. Use Excel effectively in your professional workplace and increase your productivity. About This Video Learn from a well-designed curriculum by Microsoft Excel expert in no time with this concise course Discover Pivot Table and Pivot Charts business-related examples and case studies Analyze large sets of information with exercise files to practice follow along In Detail We need to analyze data these days since we live in a very data-driven world. Therefore, data is important in any business, whether you are looking for trends or forecasting future business needs. As there is a lot of importance placed on data analysis, you must have the relevant skills to analyze data effectively. Pivot Tables is an essential Excel skill for jobs that involve analyzing and visualizing large amounts of data. Pivot Tables are an interactive way of quickly summarizing large amounts of data by grouping and aggregating data sets and analyzing data clearly and effectively. This course will discuss the importance of cleaning your data before creating your first Pivot Table. You'll also learn how to create Pivot Charts and how to format your Pivot Tables and Charts. This course includes downloadable Excel data files that the instructor uses in the guide to follow along. By the end of this course, you'll learn the skills required to be able to clean the data, put it in the Pivot Table, analyse the data efficiently, and keep it updated with a single click. Therefore, by opting for this course, you'll be able to take your own information and leverage Pivot Tables to answer questions with ease. Who this book is for This course is for anyone who works with Microsoft Excel even if you've never used data analytics, Pivot Table and Pivot Charts. This course is aimed at people who have never used Pivot Tables before and would like to get started. It is also helpful for those who understand Pivot Tables but would like to expand their Excel skills. Individuals with basic knowledge of Excel 2019/365 and those upgrading from previous software versions will also be benefitted from this course. Knowledge of MS Excel is useful but not mandatory.